PENGEMBANGAN MODUL DASHBOARD ADMIN “EPAKAN” DENGAN IMPLEMENTASI USABILITY TESTING - Astria Hijriani; Ardiansyah Ardiansyah; Tri Setiawan (Jurnal Pepadun, 2022)
The creation of application is very easy for farmers and non-farmers to buy and sell livestock products. Along with the creation of the application and the existence of a business process in it is needed a system that can be a connection between the application and its users. The presence of a dashboard system is expected to help admin performance in handling some business activities in ePakan. In its development the dashboard system was built using the PHP programming language with Laravel Framework. The methods used for system development use Extreme Programming. The features in this ePakan dashboard include, payment confirmation, account verification, balance disbursement, transaction logging. Based on The results of the dashboard testing the ePakan works as needed and based on testing user satisfaction usability, the dashboard system gets an average value of 83% which means it is very good.